SATISFACTION OF MEDICAL STAFF IN PRIMARY HEALTH CARE OF SUMADIA DISTRICT - Radevic, Svetlana R (Medicinski časopis, 2015)
Objective. The aim of this study was to evaluate different aspects of job satisfaction among employees as well as to evaluate the overall job satisfaction in health care institutions of the primary health care level in Shumadia district. Methods. Employee satisfaction survey was conducted in 10 primary health facilities in Sumadia district. We conducted a one-day survey of 1273 employees, using a uniform, anonymous questionnaire developed by the Ministry of Health of the Republic of Serbia within the program of improvement of the quality of health care facilities functioning. Results. The data we obtained, show that a little less than half of employees in health institutions of the Republic of Serbia is satisfied with the work they performe. Results of logistic regression showed that a statistically significant impact on the assessment of job satisfaction have the following factors examined: adequacy of work equipment, possibility of professional development, support by superiors, comparison of satisfaction of 5 years ago and now. Conclusion. The job related experience and satisfaction of the employees, indicates the need for placement of employee satisfaction on priority in the process of improving the quality of the health care system. Keywords : employee satisfaction, primary health care, Shumadia region